Evaluation Model and Application of Shale Oil Production Efficiency Under Energy-Depleted Development Mode in Jimsar Sag - Gao, Yang; Zhi, Dongming; Li, Yingyan; Jiang, Zhenxue; Deng, Yuan; Qin, Jianhua (Frontiers in Energy Research, 2022)
In order to reveal the shale oil production mechanism and production efficiency of energy-depleted development mode under geological conditions, the experiments of expulsion oil based on imbibition and elastic energy release under high temperature and pressure were carried, and NMR on-line monitoring was used to observe the production characteristics of shale oil under different oil expulsion mechanisms. The experimental results show that the imbibition-expulsion oil mainly occurs in the small-size pore-throat system. Under the condition of high temperature and pressure, affected by the fluid pressure in pores, the oil-expulsion efficiency is generally low, less than 2%, which is significantly different from the conventional imbibition experiment results. Although elastic-energy expulsion oil occurs in different size pore-throat systems, the oil-expulsion efficiency in large size pore-throat systems is more sensitive to temperature. Overall, the total elastic-energy oil-expulsion efficiency is significantly positively correlated with reservoir physical properties, production differential pressure and temperature, and negatively correlated with crude oil viscosity. Comprehensively considering various geological factors affecting oil-expulsion efficiency, the shale oil production efficiency evaluation model under the energy-depleted development mode is constructed, and the movable oil porosity of shale oil development section in the study area is evaluated. The results show that there is a good positive correlation between movable oil porosity and oil production intensity. When the movable oil porosity is less than 0.5%, it is basically a dry layer, between 0.5% and 1.5% is a poor oil layer, between 1.5% and 2.5% is a type II oil layer, and greater than 2.5% is a type I oil layer. The single well evaluation results show that the shale oil “sweet spot” of Lucaogou Formation in Jimsar Sag is mainly distributed in P2l22-1 P2l22-3 and P2l12-1 P2l12-3, which is in good agreement with the current development status.